Local immunity by tissue-resident CD8+ memory T cells - Gebhardt, Thomas; Mackay, Laura K. (Frontiers in Immunology, 2012)
Microbial infection primes a CD8+ cytotoxic T cell response that gives rise to a long-lived population of circulating memory cells able to provide protection against systemic reinfection. Despite this, effective CD8+ T cell surveillance of barrier tissues such as skin and mucosa typically wanes with time, resulting in limited T cell-mediated protection in these peripheral tissues. However, recent evidence suggests that a specialized subset of CD103+ memory T cells can permanently lodge and persist in peripheral tissues, and that these cells can compensate for the loss of peripheral immune surveillance by circulating memory T cells. Here, we review evolving concepts regarding the generation and long-term persistence of these tissue-resident memory T cells (TRM) in epithelial and neuronal tissues. We further discuss the role of TRM cells in local infection control and their contribution to localized immune phenomena, in both mice and humans.